(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2024)
Purpose: The purpose of this study is to examine and compare the stress levels experienced by employees in public versus private sector banks in Kerala. It aims to identify the key factors contributing to stress in both sectors and evaluate the impact of these factors on employees’ stress levels. Methodology: The study employs a comparative research design and samples employees from five selected banks, utilizing structured questionnaires for data collection. The analysis incorporates both descriptive and inferential statistical methods, including Chi-square tests, T-tests, and Structural Equation Modeling (SEM), to assess stress levels and identify significant stressors. Results/Analysis: The findings indicate that employees in both public and private sector banks experience moderate stress, with an average stress level of 48.33%. Major stressors identified include workload, bureaucratic processes, and competitive targets. The analysis reveals that current stress levels exceed expectations, highlighting the need for effective stress management strategies. Originality/Value: This research offers valuable insights by providing a comparative perspective on stress levels in different banking sectors and exploring the impact of organizational culture and support systems. The study contributes to the development of tailored stress management interventions for the banking sector. Type of Paper: Empirical Research Paper.